PENGARUH IMPLEMENTASI TEKNIK SYSTEMATIC DESENSITIZATION AND GENERALIZATION OF OPERANT STIMULUS DALAM MENURUNKAN POST TRAUMATIC STRESS DISORDER ANAK KORBAN KEKERASAN SEKSUAL DI SENTRA PHALAMARTA SUKABUMI - Sumaki, Septyan Berliana; Subardhini , Meiti; Santi, Kanya Eka (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Sexual violence is a serious problem that is worldwide, threatens human rights, and has very damaging impacts, one of which is causing post-traumatic stress disorder. This research aims to obtain an empirical picture and conduct an analysis of the effect of implementing systematic desensitization and generalization of operant stimulus techniques in reducing post-traumatic stress disorder. The processes in the systematic desensitization and generalization of operant stimulus technique are designed to help individuals or children reduce the post-traumatic fear they have experienced, involving the surrounding environment in the process of reducing the hierarchy of fears experienced by the individual. The research subjects were beneficiaries at Sentra Phalamatha Sukabumi, namely three teenagers aged 14-16 years who had problems with sexual violence and post-traumatic stress disorder. The post-traumatic stress disorder that is targeted are aspects of re-experiencing (looking away), avoidance (behavior of asking the instructor during skills activities), hyperarousal (behavior of teasing friends when doing skills activities) and social (behavior of carrying out instructions from the skills instructor). The research was conducted using a quantitative approach, single subject design method with multiple baseline cross subject A-B-A design. Data collection techniques use observation techniques, giving questionnaires, interviews and documentation studies. Test the validity of the questionnaire using face validity to the supervisor while recording events by calculating the percent agreement. Measurements were carried out on target behavior with the assumption that there would be a reduction in post-traumatic stress disorder experienced by child victims of sexual violence and through questionnaires given to three research subjects by comparing the questionnaire answer scores before and after the intervention to determine the level of post-traumatic stress disorder experienced. by child victims of sexual violence. The research results showed that the systematic desensitization and generalization of operant stimulus technique had an effect on reducing target behavior, thus indicating a decrease in post-traumatic stress disorder in the three research subjects. This is shown through the trend in the direction of the graph and the results of data analysis both within conditions and between conditions from observation data on target behavior as well as an increase in quantitative values ​​or questionnaire answer scores between before and after the intervention of the three research subjects KEYWORDS: Systematic Desensitization and Generalization of Operant Stimulus Technique, Child Victims of Sexual Violence, Post Traumatic Stress Disorder, Single Subject Design